Unintentional Poisoning: Experience at a Medical Unit - Muhammad Khurram , Najia Mahmood , Nadeem Ikram (Journal of Rawalpindi Medical College, 2010)
Background: To note types of acute unintentional poisoning in patients presenting to Medical emergency of Rawalpindi Medical College, Rawalpindi. Methods: This cross sectional observational study; was conducted in a Medical unit of Rawalpindi Medical College from January to December 2006. Adult, unintentional poisoning (when a subject poisoned him/herself without an intention to be harmed) cases presenting to medical emergency were included. Each patient was managed in standard way. Type of poisoning, and outcome (death or discharge) of each patient were noted. Results: Twenty-eight patients were managed during the study period. Majority (60.7%) of patients were female. Mean patient age was 25.68±11.39 years. Snake bite (25%), various medicines like benzodiazepines and analgesics/NSAIDS (21.4%), organophosphate (17.9%), and corrosive intake (17.9%) were most frequently noted types of unintentional poisoning. Poisoning related mortality was 7.1%. Conclusion: Snake bite and various medicines like benzodiazepines and analgesics/NSAIDS are commonest types of unintentional poisoning.